Nano-encapsulated active protein AMPK inhibits cartilage matrix degradation in experimental osteoarthritis rats via SIRT1-regulated nexilin expression nano-AMPK inhibits cartilage matrix degradation - X You; LQ Wu; LL Fu; QQ Wu; BR Qi (European Cells & Materials)
Background: Osteoarthritis (OA) is characterized by progressive cartilage matrix degradation. Although adenosine monophosphate-activated protein kinase (AMPK) shows promise in treating OA, its clinical application is limited by poor bioavailability. Nano-encapsulation may overcome this limitation, but the underlying molecular mechanisms remain unclear. Methods: OA was induced in rats using the anterior cruciate ligament transection (ACLT) model, followed by intra-articular injection of nano-AMPK. Cartilage degradation was assessed by Masson staining and immunohistochemistry. The molecular mechanism was investigated using interleukin-1 beta (IL-1β)-induced rat chondrocytes, with or without sirtuin 1 (SIRT1) inhibitor (EX527) treatment and Nexilin silencing. The expression of cartilage matrix components, degradative enzymes, and signaling molecules was analyzed by Western blot and quantitative real-time polymerase chain reaction (qRT-PCR). Results: Nano-AMPK treatment significantly reduced cartilage degradation in ACLT rats, which was evidenced by increased collagen type II alpha 1 chain (COL2A1) and aggrecan expression and decreased matrix metalloproteinase (MMP)-3, MMP-13, and a disintegrin and metalloproteinase with thrombospondin motifs (ADAMTS) levels. In vitro studies revealed that nano-AMPK protected against IL-1β-induced matrix degradation by upregulating SIRT1 and Nexilin expression. Either SIRT1 inhibition or Nexilin silencing abolished the protective effects of nano-AMPK, indicating that the SIRT1-Nexilin pathway mediates nano-AMPK’s chondroprotective effects. Conclusions: This study demonstrated that nano-encapsulated AMPK effectively prevented cartilage matrix degradation in experimental OA through a previously unidentified SIRT1-regulated Nexilin pathway, providing new insights into OA treatment strategies.